Die Bildung der Generalistinnen und Generalisten Perspektiven auf Fachlichkeit im Studium zur Lehrperson für Kindergarten und Primarschule. Festschrift für Frau Prof. Dr. Charlotte Müller - Bachmann, Sara; Bertschy, Franziska; Künzli David, Christine; Leonhard, Tobias; Peyer, Ruth (Studien zur Professionsforschung und Lehrerbildung, 2021)
Specialisation is a central aspect of pedagogical professionalism. But how is (subject) study structured for teachers at the early school stage who, as generalists, later teach (almost) everything? How is subject-specificity contoured when teaching is essentially linked to the life and experience of the pupils and strives for a differentiation of perspectives in the sense of basic subject-specific education? In this volume, contours of a study programme for generalists are developed, which systematically mediate between a disciplinary academic study structure and the generalist professional requirements from the perspective of the study subjects and possible connecting concepts.